Akulovsky P.S., Katyatkin K.S. – participants of the Great Patriotic War of 1941–1945 - Lukishin A. V., Lukishina S. A. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article describes the fate of participants in the Great Patriotic War of 1941–1945, natives of the Alatyr region Akulovsky Pyotr Stepanovich and Katyatkin Konstantin Stepanovich, their front-line biographies and contribution to the cause of the Great Victory. The article is based on the materials of the Akulovsky-Lukishin family archive.
Keywords: Великая Отечественная война; семья; память; Great Patriotic War; family; поколения; memory; ветераны; veterans; generations